Blended Learning During Pandemic: EFL Undergraduate Students’ Satisfaction - Ni Wayan Tasya Astri Prawisanthi; I Gede Yoga Permana (Jayapangus Press, 2022)
The objective of this research is to investigate the EFL students’ satisfaction on the implementation of blended learning at STKIP Agama Hindu Singaraja This research is a quantitative survey. The sample of this research was 76 undergraduate students of English education department STKIP Agama Hindu Singaraja. The data were gathered by using 5-point Likert scale questionnaire. The questionnaire validity and reliability checked and showed that the questionnaire was valid and had a high reliablity. The data were analysed by using quantitative with SPSS program. The findings showed that students were very saisfied toward the implementation of blended learning (M=4.03, SD=.759). In conclusion, blended learning could be implemented in today’s Covid-19 pandemic situation as it provides more opportunity for students to engage in learning process.